Non-Muslims and Sharia-Based Regional Government; Comparison between Aceh, Indonesia and Selangor, Malaysia - Harahap, Burhanudin; Handayani, I Gusti Ayu Ketut Rachmi; Lego Karjoko (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
One plausible challenge that may emerge throughout the application of sharia law in Aceh, for instance, is the presence of interreligious disputes. The fact that not all members of communities are Muslims poses an inquiry. This research examines how Sharia law is enforced in Aceh; how legal protection for non-Muslims is affected by the enforcement, as well as, to the same topic, how the comparison between Aceh and of Selangor, Malaysia is. According to this empirical study, Qanun was created in Aceh to secure adherence to sharia law, so that Qanun Jinayat applies to community members identified as Muslim. In contrast, Malaysia is a multiethnic and multiracial nation governed by the supreme law, namely the Federal Constitution, which protects its diverse religion and communities. Sharia law applies exclusively to Muslims in Selangor, in stark contrast to jinayah law in Aceh which apply this to Aceh citizen. Hence, stakeholders in Aceh must collaborate to assess and fortify legal safeguards for non-Muslim inhabitants, extending beyond the freedom to select the form of justice they prefer. The objective is to guarantee the rights of each citizen in a manner that is devoid of violence or any indications of human rights violations.